FEATURES OF SHAPING THE IMAGE OF A MODERN UNIVERSITY - Horbenko, Nataliia V. (Educological discourse, 2014)
The article deals with the peculiarities of forming the image of the modern university, in particular, presents its definition and its components, the essence of creation and monitoring, emphasized the need for the introduction of image management in a modern marketing system of the university.